2017
DOI: 10.1155/2017/7203458
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of NR2B Contributes to Chronic Migraines via Increased Expression of CGRP in Rats

Abstract: Tyrosine phosphorylation of NR2B (NR2B-pTyr), a subunit of the N-methyl-D-aspartate (NMDA) receptor, has been reported to develop central sensitization and persistent pain in the spine, but its effect in chronic migraines has not been examined. We hypothesized that tyrosine phosphorylation of NR2B contributes to chronic migraines (CM) through calcitonin gene-related peptide (CGRP) in rats. Ninety-four male Sprague-Dawley rats were subjected to seven inflammatory soup (IS) injections. In a subset of animals, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Concentrations of calcitonin gene-related peptide (CGRP) levels, which are elevated in obese individuals [ 15 ], are a very important mediator of migraine/chronic migraine, and CGRP inhibitors are effective in the treatment of migraine. Additionally, inflammation has been proposed as a possible contributing mechanism for migraine attacks and obesity itself is proinflammatory by the increase in the concentrations of circulating cytokines [ 16 18 ]. Furthermore, migraines, like obesity, have been reported as a risk factor for cardiovascular disorders, as well as for stroke [ 6 , 7 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of calcitonin gene-related peptide (CGRP) levels, which are elevated in obese individuals [ 15 ], are a very important mediator of migraine/chronic migraine, and CGRP inhibitors are effective in the treatment of migraine. Additionally, inflammation has been proposed as a possible contributing mechanism for migraine attacks and obesity itself is proinflammatory by the increase in the concentrations of circulating cytokines [ 16 18 ]. Furthermore, migraines, like obesity, have been reported as a risk factor for cardiovascular disorders, as well as for stroke [ 6 , 7 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The von Frey test was performed on the hind paws ipsilateral to the surgery and at the midline of the forehead where the ophthalmic nerve distributed as described previously. 53 , 54 A positive response for the von Frey test was recorded when the rat retracted its head or hind paw from the rigid tip. Mechanical allodynia was evaluated before IS or PBS infusion and 24 h after I.C.V injection of the vehicle, PNU-282987 or α-bungarotoxin.…”
Section: Methodsmentioning
confidence: 99%
“…CM animal models have shown increased CGRP gene expression in rodents pain processing areas such as trigeminal nucleus caudalis [116,117]. GTN induced model showed that animal behavioral changes in pain perception correlated with an increased gene expression of CGRP in the medulla-pons region, cervical spinal cord and trigeminal ganglia [118], while it has not been demonstrated after acute GTN administration [119], supporting CGRP contribution in central sensitization.…”
Section: Animal Modelsmentioning
confidence: 99%